Second Front in Europe: Analyzing Coverage in British Regional Press - C. Kaygusuz; Yu. G. Kokorina; M. M. Vagabov (Научный диалог)
This study examines the representation of the opening of the Second Front in the British regional press, focusing on an analysis of 20 newspaper issues. The research draws upon editions of the Western Mail from June 1944, introducing this previously untranslated source into the scholarly discourse. A review of front-page articles highlights key events such as the D-Day landings, the advance of Allied forces in France, and the assault on Rome. The analysis reveals a shift in the regional pressэs emphasis, transitioning from celebratory and triumphant narratives to expressions of dissatisfaction. Notably, while the Western Mail consistently covered developments on the Western Front, it devoted only a single article to the Eastern Front. The findings indicate that through its publications, the British readership developed a perception prioritizing the Western Front in the fight against Nazi Germany, emphasizing the significance of battles in France and Italy over the liberation of the USSR and Eastern Europe. This trend contributes to the construction of a myth surrounding the Anglo-American victory over Germany. The authors argue that such coverage patterns in periodicals serve as a foundation for distorting historical truth.